Equity Crowdfunding in Germany and the UK: Follow-up Funding and Firm Survival - Lars Hornuf; Matthias Schmitt (Center for Economic Studies and ifo Institute (CESifo), 2017)
Today, start-ups often obtain financing via the Internet through many small contributions of non-sophisticated investors. Yet little is known about whether these start-ups can ultimately build enduring businesses. In this paper, we hand-collected data from 38 different equity crowdfunding (ECF) portals and 656 firms that ran at least one successful ECF campaign in Germany or the United Kingdom. The evidence shows that German firms that receive ECF stand a higher chance of obtaining follow-up funding through business angels or venture capitalists and have a relatively lower likelihood to survive. We find firm age, the average age of the management team, and excessive funding during the ECF campaign all have a negative effect on firms' likelihood to obtain post-campaign financing. By contrast, the number of senior managers, registered trademarks, subsequent successful ECF campaigns, crowd exits, and the amount of the funding target all have a positive impact. Subsequent successful ECF campaigns, crowd exits, and the number of venture capital investors are significant predictors reducing firm failure. Finally, we find that some of these factors have a differential impact for Germany and the United Kingdom.
Keywords: G24; M13; 330; equity crowdfunding; follow-up funding; firm survival